Covid 19: Antara Angka Kematian dan Angka Kelahiran - Tuti Marjan Fuadi; Irdalisa (Program Studi Sosiologi Agama Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia, 2020)
This paper aims to see the phenomenon of increasing mortality rates and birthrates during the Covid 19 pandemic. Pandemic Covid 19 has a lot of life, the number of victims worldwide reached 1.49 million people, and Indonesia as many as 17.199 people. To break the chain of the spread of the coronavirus, the Indonesian government has implemented a Large-Scale Social Restriction (PSBB) policy. The PSBB policy taken by the government at least influenced the increase in pregnancy rates, so a baby boom was predicted in 2021. The data in this paper comes from literature studies and relevant online newspapers. The results of this study are; 1) The cause of the high death rate due to Covid-19 is caused by individual factors and external factors. 2) The death rate has reached 17,081 with the number of cases 543,975 where Male groups are more prone to becoming victims of Covid 19 than women. Covid-19 victims in men are 55% higher than women. The high number of men exposed to Covid 19 is influenced by biological factors and social factors. 3) The birth rate has increased due to several supporting factors i.e the implementation of PSBB by the government resulted in more time with family, which led to an increase in pregnancy rates. Furthermore, access to health services is difficult so that many married couples do not visit health services for contraceptive programs until many women conceding and unplanned pregnancies.